Effect of non-conjugate and conjugate condition on heat transfer from the battery pack - Mokashi, Imran; Afzal, Asif; Al-Mdallal, Qasem; Sundar, L. Syam; Khan, Sher Afghan; Abdullah, Nur Azam; Azami, Muhammad Hanafi; Saleel, C Ahamed (Elsevier Ltd Kidlington Corporate Office, Kidlington, United Kingdom, 2021)
Li-ion battery packs provide high energy density but with a concern of thermal management. Hence cooling mechanism is necessary to have a good life and reliability on the battery system. The main objective of this article is to investigate the effect of conjugate and non-conjugate boundary conditions on battery pack heat transfer characteristics. In conjugate conditions, coolant flow is considered with heat flux continuity at the battery and fluid interface. In non-conjugate condition, just convection condition is adopted. The finite volume method is adopted for the numerical analysis, and a code is written for computations of the governing equations. Effects of different parameters like heat generation, conductivity ratio, coolants, and Biot number on temperature distribution in the battery pack are analyzed. The maximum temperature contours are located near the top end of the battery, whereas at the bottom end, the battery’s temperature is low. Such high and low-temperature regions in the battery pack create uneven thermal stresses, resulting in battery failure. To have better performance results for the battery system, one should maintain the proper balance of thermal conductivity between the solid and fluid domains. From the comparative analysis, it is found that the non-conjugate condition gives the temperature distribution in the battery to be of symmetrical nature and more uniform. Practically, this is not true which is confirmed by the realistic conjugate condition where the high-temperature zones are closer to the trailing edge of the battery pack. Liquid metals and nanofluids provide a much safer operating temperature of the pack where the maximum temperature is well below the critical temperature. The application of conjugate conditions for battery thermal analysis leads to having an insight of the hotspot zones accurately which are operated using conventional fluids mentioned in this work.